Anaesthetic consideration for caesarean delivery of a parturient without 'The Master Gland' - Tuhin Mistry; Sushil Bhati; Chandra Sekhar Chatterjee; Rama Chatterjee (Wolters Kluwer Medknow Publications, 2015)
We are presenting the management of a patient posted for elective caesarean delivery who conceived after ovulation induction and in vitro fertilisation, 20 years after postsurgical hypopituitarism. She had uneventful pregnancy and delivered a healthy baby by caesarean section under general anaesthesia.